High cycling cadence reduces carbohydrate oxidation at given low intensity metabolic rate - Ralph Beneke; Ahmad Alkhatib (Termedia Publishing House, 2014)
Cycling cadence (RPM)-related differences in blood lactate concentration (BLC) increase with increasing exercise intensity, whilst corresponding divergences in oxygen uptake ( ·VO2) and carbon dioxide production ( ·VCO2) decrease. Aim of the present study was to test whether a higher RPM reduces the fraction  (%) of the ·VO2 used for carbohydrate oxidation (relCHO) at a given BLC. Eight males (23.9 ± 1.6 yrs; 177 ± 3 cm; 70.3 ± 3.4 kg) performed incremental load tests at 50 and 100 RPM. BLC, ·VO2 and ·VCO2 were measured. At respiratory exchange ratios (RER) < 1, relCHO were calculated and the constant determining 50 % relCHO (kCHO) was approximated as a function of the BLC. At submaximal workload ·VO2, ·VCO2, and relCHO were lower (all p 0.209) at 50 than at 100 RPM. No differences were observed in ·VO2peak (3.96 ± 0.22 vs. 4.00 ± 0.25 l · min-1) and RERpeak (1.18 ± 0.02 vs. 1.15 ± 0.02). BLC was lower (p < 0.001; η² = 0.680) at 50 than at 100 RPM irrespective of cycling intensity. At 50 RPM, kCHO (4.2 ± 1.4 (mmol · l-1)3) was lower (p = 0.043; η² = 0.466) than at 100 RPM (5.9 ± 1.9 (mmol · l-1)3). This difference in kCHO reflects a reduced CHO oxidation at a given BLC at 100 than at 50 RPM. At a low exercise intensity, a higher cycling cadence can substantially reduce the reliance on CHO at a given metabolic rate and/or BLC.